2020
DOI: 10.1017/s1355617720000132
|View full text |Cite
|
Sign up to set email alerts
|

Performance Validity Testing in Justice-Involved Adults with Fetal Alcohol Spectrum Disorder

Abstract: Objectives: A number of commonly used performance validity tests (PVTs) may be prone to high failure rates when used for individuals with severe neurocognitive deficits. This study investigated the validity of 10 PVT scores in justice-involved adults with fetal alcohol spectrum disorder (FASD), a neurodevelopmental disability stemming from prenatal alcohol exposure and linked with severe neurocognitive deficits. Method: The sample comprised 80 justice-involved adults (ages 19–40) includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 78 publications
(126 reference statements)
0
10
0
Order By: Relevance
“…They described that only a few participants became involved with the justice and/or the legal system. A deficit in IQ was reported by Mullay et al, who described IQ values <70 in the FASD group [ 37 ]. These data were confirmed by Brownell et al [ 34 ].…”
Section: Resultsmentioning
confidence: 91%
“…They described that only a few participants became involved with the justice and/or the legal system. A deficit in IQ was reported by Mullay et al, who described IQ values <70 in the FASD group [ 37 ]. These data were confirmed by Brownell et al [ 34 ].…”
Section: Resultsmentioning
confidence: 91%
“…A total of nine cross sectional studies involving 766 participants were included in the review. Of those, seven studies were conducted in Canada (Brintnell et al., 2019; Flannigan et al., 2019; Harker, 2014; McLachlan et al., 2019; Mullally et al., 2020; Xiao, 2018), and the other two in Australia (Bower et al., 2018). Only three studies involved youths aged 10–17 (Bower et al., 2018; Harker, 2014; Kippin et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The protocol for diagnosis of FASD is specified in eight studies, which either followed the Canadian (Chudley et al., 2005) or the Australian (Bower et al., 2017) diagnostic guidelines for FASD. Two studies (Kippin et al., 2018; Mullally et al., 2020) entailed secondary analysis of data from two of the other included studies (Bower et al., 2017; McLachlan et al., 2019). There was inconsistency in the reporting of comorbidities and medications; most of the included studied provided no data on these (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…During forensic evaluation, acquiescence bias can have a profound impact on self‐report accuracy in questionnaires and inventories as well as interviews. For example, Mullally, McLachlan, MacKillop, and Pei (2020) compared the validity of 10 commonly used performance validity tests (PVTs) in 80 justice‐involved adults, 25 with confirmed or possible FASD, and 55 where FASD was ruled out. Results indicated that compared to neurotypical participants, those with diagnosed and possible FASD were more likely to fail any single PVT and failed a greater number of PVTs.…”
Section: Social Vulnerability and Response Biasmentioning
confidence: 99%
“…Even if offense‐relevant information has been successfully stored, a need to access that information requires intact cause‐and‐effect reasoning and ability to make logical inferences about memories that are relevant to the offense. Notably, research shows that because of the widespread cognitive dysfunction in FASD, this population generally exhibits high rates of impairment on standardized testing of legal capacities relevant to interrogation and adjudication (Mullaly et al., 2020). For example, a study that addressed psycholegal abilities in young offenders with FASD (McLachlan et al., 2014) found that 90% of the study population showed impairment in at least one psycholegal ability.…”
Section: Social Vulnerability and Response Biasmentioning
confidence: 99%